Titania-functionalized graphene oxide for an efficient adsorptive removal of phosphate ions - Samita Sakulpaisan (2018)
© 2015 Elsevier Ltd. Titania-functionalized graphene oxide (T-F GO), synthesized by a sol-gel process, was used as a highly efficient material to remove phosphate ions from the simulated wastewater. X-ray diffraction spectra, Fourier transform infrared spectra and scanning electron micrographs of T-F GO confirmed that titania particles were successfully grown on graphene oxide (GO) surface. The phosphate ion adsorption capacities of GO, titania and T-F GO as a function of the contact time and the pH were investigated by a UV-visible spectrophotometer. Results showed that T-F GO could absorb phosphate ions better than titania and GO could. This indicated the synergistic effect between titania and GO in the phosphate ion adsorption. The pH increment lowered the absorption capacities due to increasing the repulsion between phosphate anions and the charges on the T-F GO surface, whereas the addition of sodium ions increased the adsorption capacities. Also, phosphate ions were absorbed by specific sites of T-F GO and formed a monolayer on its surface. Finally, the maximum adsorption capacity of T-F GO was 33.11 mg/g at pH 6, much higher than those of GO and titania. Therefore, T-F GO could be a promising material to remove phosphate ions from wastewater in the future.